2017
DOI: 10.1021/acs.jafc.7b04167
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Zanthoxylum Species Based on Integrated Analysis of Complete Chloroplast Genome Sequences and Metabolite Profiles

Abstract: We performed chloroplast genome sequencing and comparative analysis of two Rutaceae species, Zanthoxylum schinifolium (Korean pepper tree) and Z. piperitum (Japanese pepper tree), which are medicinal and culinary crops in Asia. We identified more than 837 single nucleotide polymorphisms and 103 insertions/deletions (InDels) based on a comparison of the two chloroplast genomes and developed seven DNA markers derived from five tandem repeats and two InDel variations that discriminated between Korean Zanthoxylum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Most of these markers were derived from the intergenic regions of cp genomes and showed high interspecific polymorphism. Previous molecular identification of Panax , Zanthoxylum , and Eclipta species also indicated that chloroplast-derived genetic markers had high discriminatory powers [ 12 , 14 , 48 ]. Therefore, specific markers developed from the comparative cp genomes were superior than the commonly used markers for identifying the closely related species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these markers were derived from the intergenic regions of cp genomes and showed high interspecific polymorphism. Previous molecular identification of Panax , Zanthoxylum , and Eclipta species also indicated that chloroplast-derived genetic markers had high discriminatory powers [ 12 , 14 , 48 ]. Therefore, specific markers developed from the comparative cp genomes were superior than the commonly used markers for identifying the closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast (cp) genome of angiosperm is characterized by a typical quadripartite structure that contains a pair of inverted repeat (IR) regions separated by a large single-copy (LSC) and a small single-copy (SSC) region [ 13 ], and it is highly conserved compared to nuclear and mitochondrial genomes. Although chloroplast genomes are highly conserved, some hotspot regions with single nucleotide polymorphisms and insertion/deletions could be found and these regions may provide enough information for species identification [ 14 , 15 ]. Due to low recombination, uniparental inheritance, and low nucleotide substitution rates, many cp genetic markers have been used for plant phylogenetic, phylogeographic, and population genetic analyses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A valid alternative to nuclear DNA-based analysis is the use of approaches involving the chloroplast genome, which is present in high copy numbers in vegetal cells. Indeed, heavily industrial treatments can severely affect nuclear DNA quality and quantity, while this occurs to a lesser extent with chloroplast DNA due to its abundance [ 62 , 63 ].…”
Section: Advantages and Limits Of Molecular Methods In Agri-food Authentication And Traceabilitymentioning
confidence: 99%
“…The sequencing of chloroplast genome produces reads that can be compared to specific databases containing complete chloroplast genome sequences such as the GenomeTrakrCP, which is publicly available at the National Center for Biotechnology Information ( ; accessed on 24 May 2021) [ 115 ]. This approach has been demonstrated to be highly effective by several authors [ 62 , 63 ].…”
Section: Molecular Approaches To Agri-food Analysismentioning
confidence: 99%
“…The development of molecular markers has also become cost effective through comparisons of cp genomes. The complete cp genomes of several Zanthoxylum species have been sequenced by de novo assembly using a small amount of whole-genome sequencing data [18][19][20].…”
Section: Introductionmentioning
confidence: 99%